A Novel Dry Model for Practicable Sphincterotomy and Precut Needle Knife Sphincterotomy - Akio Katanuma; Takao Itoi; Junko Umeda; Ryosuke Tonozuka; Shuntaro Mukai; Kei Yane; Toshifumi Kin; Kazuaki Matsumoto; Tomoaki Matsumori; Katsushige Gon; Ryo Takaki; Akiko Tomonari (Gastroenterology Research and Practice)
Aim. We aimed to develop a simulation dry model for endoscopic sphincterotomy (ES) and needle knife precut sphincterotomy (NKP) and to evaluate its usefulness as a training simulator. Materials and Methods. An endoscopic retrograde cholangiopancreatography trainer was used as a duodenum, bile duct, and papilla simulator. A simulated papilla was created with a piece of rolled uncured ham, and ES and NKP were performed. Hands-on training was carried out using this model, and success and failure of the procedures were evaluated. A questionnaire survey was conducted among the participants to assess the performance and usefulness of the dry model for ES and NKP training. Results. Twenty-two endoscopists participated in the hands-on training using this dry model. ES was successful in 33 out of 34 attempts (97%) whereas NKP was successful in all 7 attempts (100%). Based on the results of the questionnaire survey, the median score for realism was 7 (range: 2–9) for ES and 8 for NKP on a scale of 1 to 10. Conclusions. The dry model using an uncured ham provides a condition closely similar to actual clinical practice and is useful as a training model for ES and NKP.